The absence of the Pseudomonas aeruginosa OprF protein leads to increased biofilm formation through variation in c-di-GMP level - Bouffartigues, Emeline; Moscoso, Joana A.; Duchesne, Rachel; Rosay, Thibaut; Fito-Boncompte, Laurène; Gicquel, Gwendoline; Maillot, Olivier; Bénard, Magalie; Bazire, Alexis; Brenner-Weiss, Gerald; Lesouhaitier, Olivier; Lerouge, Patrice; et al. (Frontiers in Microbiology, 2015)
OprF is the major outer membrane porin in bacteria belonging to the Pseudomonas genus. In previous studies, we have shown that OprF is required for full virulence expression of the opportunistic pathogen Pseudomonas aeruginosa. Here, we describe molecular insights on the nature of this relationship and report that the absence of OprF leads to increased biofilm formation and production of the Pel exopolysaccharide. Accordingly, the level of c-di-GMP, a key second messenger in biofilm control, is elevated in an oprF mutant. By decreasing c-di-GMP levels in this mutant, both biofilm formation and pel gene expression phenotypes were restored to wild-type levels. We further investigated the impact on two small RNAs, which are associated with the biofilm lifestyle, and found that expression of rsmZ but not of rsmY was increased in the oprF mutant and this occurs in a c-di-GMP-dependent manner. Finally, the extracytoplasmic function (ECF) sigma factors AlgU and SigX displayed higher activity levels in the oprF mutant. Two genes of the SigX regulon involved in c-di-GMP metabolism, PA1181 and adcA (PA4843), were up-regulated in the oprF mutant, partly explaining the increased c-di-GMP level. We hypothesized that the absence of OprF leads to a cell envelope stress that activates SigX and results in a c-di-GMP elevated level due to higher expression of adcA and PA1181. The c-di-GMP level can in turn stimulate Pel synthesis via increased rsmZ sRNA levels and pel mRNA, thus affecting Pel-dependent phenotypes such as cell aggregation and biofilm formation. This work highlights the connection between OprF and c-di-GMP regulatory networks, likely via SigX (ECF), on the regulation of biofilm phenotypes.